2009
DOI: 10.1007/s10531-009-9592-8
|View full text |Cite
|
Sign up to set email alerts
|

Preserving genetic integrity in a hybridising world: are European Wildcats (Felis silvestris silvestris) in eastern France distinct from sympatric feral domestic cats?

Abstract: We investigate the genetic profile of putative European Wildcats in northeastern France, possessing the wildcat phenotype, but sampled in an area where they are sympatric with free-roaming domestic cats and, thus, are exposed to potential hybridisation. From a sample of 209 cats, the programme STRUCTURE clearly identified two distinct genetic clusters that corresponded to European Wildcats and domestic cats. The cats from these two clusters were clearly differentiated from each other (F ST = 0.16). However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 28 publications
2
57
1
1
Order By: Relevance
“…Previous studies clearly show that the development of more powerful tools is still critical to accurately identify parental and hybrid individuals of this species because of the high similarity in morphology and genomes of wild and domestic forms. Although microsatellites have been the dominant markers in wildcat genetic studies (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Lecis et al, 2006;Germain et al, 2008;Eckert et al, 2010;O'Brien et al, 2009), and recently mtDNA diagnostic SNPs have been suggested (Driscoll et al, 2011), the increasing availability and numerous advantages of nuclear SNPs make them an appealing alternative and/or a complement to maternal and paternal lineage markers. SNPs have been attracting a growing interest in a wide range of evolutionary applications and are becoming efficient tools among wildlife conservation-oriented studies (Brumfield et al, 2003;Morin et al, 2004;Seddon et al, 2005;Morin et al, 2009).…”
Section: Snp Simulations For Admixture Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies clearly show that the development of more powerful tools is still critical to accurately identify parental and hybrid individuals of this species because of the high similarity in morphology and genomes of wild and domestic forms. Although microsatellites have been the dominant markers in wildcat genetic studies (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Lecis et al, 2006;Germain et al, 2008;Eckert et al, 2010;O'Brien et al, 2009), and recently mtDNA diagnostic SNPs have been suggested (Driscoll et al, 2011), the increasing availability and numerous advantages of nuclear SNPs make them an appealing alternative and/or a complement to maternal and paternal lineage markers. SNPs have been attracting a growing interest in a wide range of evolutionary applications and are becoming efficient tools among wildlife conservation-oriented studies (Brumfield et al, 2003;Morin et al, 2004;Seddon et al, 2005;Morin et al, 2009).…”
Section: Snp Simulations For Admixture Analysismentioning
confidence: 99%
“…The survival and conservation of indigenous populations of the European wildcat might be locally threatened by introgressive hybridization with feral domestic cats (Felis silvestris catus). Over the last decade, the genotyping of highly polymorphic molecular markers (specifically microsatellites, short tandem repeats) and partial mitochondrial DNA sequences, combined with new Bayesian statistical tools, have radically improved the knowledge on wildcat population genetics and admixture with the domestic cat (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Kitchener et al, 2005;Lecis et al, 2006;Oliveira et al, 2008a, b;O'Brien et al, 2009;Hertwig et al, 2009;Eckert et al, 2010;Mattucci et al, 2013). Wildcats have been domesticated from African wildcat (F.s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lure stick method enables a DNA-based distinction between wild and domestic cat, which promises to solve the long-standing difficulty of safe discrimination under field conditions and the virtual impossibility to safely identify hybrids even under the presence of fresh roadkill material or live-trapped cats (Daniels et al 1998;Eichholzer 2010;Krüger et al 2009). As hybridisation with the omnipresent domestic cat was identified as a major threat to the scattered wildcat populations in Europe (Beaumont et al 2001;Devillard et al 2014;Nussberger et al 2014;O'Brien et al 2009;Pierpaoli et al 2003), the safe discrimination of wild and domestic cats and their hybrids poses another major advantage of lure stick-based monitoring compared to traditional survey methods.…”
mentioning
confidence: 99%
“…In relation to hybrids, it should be taken into account that the hybridization level is low for most wildcat ranges (Pierpaoli et al 2003;Oliveira et al 2008;Hertwig et al 2009;O'Brien et al 2009;Lozano and Malo 2012), with hybrids overall being fairly scarce and the number of their scats irrelevant (excepting for some places at the regional scale; see Zuberogoitia et al 2001;Pierpaoli et al 2003;Lecis et al 2006;Germain et al 2008). Furthermore, wildcats and domestic cats belong to the same species (e.g., Sunquist and Sunquist 2002;Driscoll et al 2007).…”
Section: Wildcat Scat Surveysmentioning
confidence: 99%